The yield of Limulus amoebocyte lysate (LAL), which is used for endotoxin detection and adjunct diagnosis of invasive fungal infection, was optimized with caffeine collection buffer - Zhang, Sophia; Zhang, Mengmeng; Zhang, Jessica (Frontiers in Microbiology, 2025)
BackgroundLimulus amoebocyte lysate (LAL) is a major component of the Fungal Infection Diagnosis Kit for the adjunct diagnosis of invasive fungal infections. During the previous bleeding season, PBS-collection buffer was found to prevent degranulation during the blood collection procedure. In addition, PBS-derived Limulus Amoebocyte Lysate (LAL) was used in both the chromogenic assay and the turbidimetric test. A similar phenomenon was observed with the caffeine collection buffer. This collection buffer is easy to prepare.MethodsTo further confirm these observations, we used caffeine collection buffer to collect blood from horseshoe crabs. Six crabs were bled per week, for a total of 60 crabs. Blood was collected from each crab via both caffeine collection buffer and 3% NaCl collection buffer. The cell pellets were then resuspended in LAL reagent water (LRW) or 5 mM CaCl2. The final LAL activity was tested via chromogenic tests and turbidimetric assay methods.ResultsCaffeine collection buffer prevented degranulation for more than 1 h, and the yield of caffeine-derived LAL was much greater than that of the 3% NaCl solution. Notably, caffeine-derived LAL was found to work in both chromogenic tests and turbidimetric assays. The enzyme characteristics of the LAL were also determined.ConclusionCaffeine collection buffer prevents amoebocyte degranulation during blood collection and processing. The activity of caffeine LAL is much greater. Caffeine LAL works in both chromogenic tests and turbidimetric assays.